Biorefinery approach towards greener succinic acid production from oil palm frond bagasse. Issue 10 (October 2016) - Indera Luthfi, Abdullah Amru; Jahim, Jamaliah Md.; Harun, Shuhaida; Tan, Jian Ping; Mohammad, Abdul Wahab
Graphical abstract: Highlights: Alkaline-based pretreatment of oil palm frond (OPF) bagasse was studied. Combination of alkaline pretreatment with autohydrolysis showed greater enzymatic hydrolysis performance. Sugars liberated from enzymatic hydrolysis of OPF bagasse was analyzed. The presence of formate increased succinic acid production from OPF hydrolysate. This is the first evaluation on the alkaline pretreatment followed by enzymatic hydrolysis of OPF bagasse for succinic acid production. Abstract: Oil palm frond (OPF) bagasse, being one of the cheapest biomass ever reported (19.4/t), was hydrolyzed and used as a raw material for fermentative production of succinic acid for the first time. Results indicated that glucose and xylose were released as the main carbon source after alkaline pretreatment followed by enzymatic hydrolysis. The resultant hydrolysate from the pretreated OPF bagasse was used directly as the carbon source in the fermentation without any purification. The pretreatment using alkaline followed by enzymatic hydrolysis of the OPF bagasse had revealed a total sugar yield of 50.3 g out of 100 g raw biomass. After 60 h of anaerobic batch fermentation using OPF bagasse hydrolysate, 86% of total sugar was consumed by Actinobacillus succinogenes 130Z which led to a succinic acid yield of 0.71 g/g of sugar. This indicates that the largest residue from palm oil industry, OPF bagasse, can be used effectively as a carbon source for succinic acid production. A total of 36.6 g/L of succinic acid was produced with an exogenous supply of formate at 25 mM, indicating that the re-utilization of formate in the waste stream could enhance succinic acid production.